Model Konseling Islami Berbasis Neuro-Linguistic Programming sebagai Media Dakwah dalam Meningkatkan Motivasi Belajar Siswa MAN 16 Jakarta - Zahra Aulia, Fathimah; Zanah, Mu’minatul; Anjani Hilman, Fathin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
The low motivation of students, reflected in lack of concentration and disruptions during learning, can influence their career choices and future goals. This study applies Individual Counseling with Neuro Linguistic Programming (NLP) at MAN 16 Jakarta to enhance students' learning motivation. The research aims to comprehend the individual counseling program through NLP, its implementation process, and its impact on students' learning motivation. This approach adopts the perspectives of John Grinder and Richard Bandler on NLP as a study of the interaction between the brain, language, and actions to achieve life goals. A descriptive qualitative method is employed, utilizing data collection through unmodified observations and interviews. The research findings indicate that individual counseling with NLP has a significant positive impact not only on learning motivation but also on changes in students' attitudes and thought patterns.